The university extension in times of pandemic: virtuality and community work with the Valle La Estrella Communal Emergency Committee, Limón Costa Rica - Centeno-Morales, Jacqueline (2023)
The Institute of Social Studies in Population (IDESPO) and the School of History, both academic units of the National University of Costa Rica, developed since 2020 the project “Contributions for citizen management in the face of flood risk in the community of Pandora Oeste in the Valle La Estrella Limón”, in response to community request to better manage the impact of flooding in their locality. In this way, the project proposes as a general goal “to strengthen citizen competences for community management in the face of flood risk in the community of Pandora Oeste in the Valle La Estrella Limón”, for this purpose a series of outreach activities were proposed in collaboration with the Valle La Estrella Communal Emergency Committee (CCEVA), which were interrupted as a result of the sanitary measures issued by the Government of Costa Rica, in order to reduce the spread of COVID-19. This situation caused the work team to reconsider the actions of university extension through the use of virtual tools that shorten distances, allowing the generation of new methodologies and experiences to be developed in continuous learning, thus this systematization reflects the methodological experience lived, which can be implemented in university extension processes in those localities with access to connectivity and technological tools. For this reason, this systematization is proposed, which has the objective of “Rescuing the methodological experience in university extension processes, implemented with the Communal Emergency Committee of Valle la Estrella Limón in the context of the national health emergency COVID-19, through tools of Information and Communication Technologies in order to implement new strategies in university extension”; which can be implemented in those locations that have access to connectivity and technological tools.